Culture and stigma in religion: the Westboro Baptist Church - Pimentel, Alexandra (Kansas State University, 2016)
This study examines the lived experiences of the members of the Westboro Baptist Church, a small church based in Topeka, KS and known for engaging in extensive protesting, from the perspective of stigmatization and the subcultural identity theory of religious persistence. Semi-structured interviews were conducted with members of the congregation, exploring issues of how they perceive themselves to exist in relation to broader American society. A qualitative analysis of the interviews revealed three main themes: religion as a guiding framework, members’ relationships with others, and stigma and stigma management. Members of the Westboro Baptist Church see the world through a core Biblical framework of understanding that influences both how they relate to and disengage from interactions with others and the ways in which they negotiate stigma in these interactions. This research contributes to the body of research on stigma and stigma management as well as adds theoretically to the subcultural identity theory of religion.
Keywords: Stigma; Religion; Westboro Baptist Church; Subcultural identity theory; Sociology; Qualitative